European beech dieback after premature leaf senescence during the 2018 drought in northern Switzerland. (18th October 2022) - Frei, E. R.; Gossner, M. M.; Vitasse, Y.; Queloz, V.; Dubach, V.; Gessler, A.; Ginzler, C.; Hagedorn, F.; Meusburger, K.; Moor, M.; Samblás Vives, E.; Rigling, A.; et al.
Abstract: During the particularly severe hot summer drought in 2018, widespread premature leaf senescence was observed in several broadleaved tree species in Central Europe, particularly in European beech ( Fagus sylvatica L.). For beech, it is yet unknown whether the drought evoked a decline towards tree mortality or whether trees can recover in the longer term. In this study, we monitored crown dieback, tree mortality and secondary drought damage symptoms in 963 initially live beech trees that exhibited either premature or normal leaf senescence in 2018 in three regions in northern Switzerland from 2018 to 2021. We related the observed damage to multiple climate‐ and stand‐related parameters. Cumulative tree mortality continuously increased up to 7.2% and 1.3% in 2021 for trees with premature and normal leaf senescence in 2018, respectively. Mean crown dieback in surviving trees peaked at 29.2% in 2020 and 8.1% in 2019 for trees with premature and normal leaf senescence, respectively. Thereafter, trees showed first signs of recovery. Crown damage was more pronounced and recovery was slower for trees that showed premature leaf senescence in 2018, for trees growing on drier sites, and for larger trees. The presence of bleeding cankers peaked at 24.6% in 2019 and 10.7% in 2020 for trees with premature and normal leaf senescence, respectively. The presence of bark beetle holes peaked at 22.8% and 14.8% in 2021 for trees with premature and normal leaf senescence, respectively. Both secondary damage symptoms occurred more frequently in trees that had higher proportions of crown dieback and/or showed premature senescence in 2018. Our findings demonstrate context‐specific differences in beech mortality and recovery reflecting the importance of regional and local climate and soil conditions. Adapting management to increase forest resilience is gaining importance, given the expected further beech decline on dry sites in northern Switzerland. Abstract : Tree and crown mortality in European beech after the 2018 hot drought were more pronounced for trees that showed premature leaf senescence in 2018, for trees growing on drier sites, and for larger trees.